2021
DOI: 10.1371/journal.pone.0252481
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and the COVID-19 pandemic: Severity of symptoms and associated factors among university students after the end of the movement lockdown

Abstract: Background and aims This online cross-sectional study investigated the severity of depressive, anxiety, and stress symptoms among university students and determined the association between various factors and the levels of depressive and anxiety symptoms in response to the coronavirus disease 2019 (COVID-19) pandemic after the movement control order (MCO) was lifted. Methods A total of 316 participants were administered a self-report questionnaire that collected data on sociodemographic attributes, personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 37 publications
(67 reference statements)
11
53
2
4
Order By: Relevance
“…Pre-existing mental health problems have been predicted to affect students' current outcomes during the COVID-19 pandemic ( 33 ). Social support from family or friends could also affect University students' mental health problems ( 34 ). Therefore, longitudinal methods should be employed to further address temporal changes in their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing mental health problems have been predicted to affect students' current outcomes during the COVID-19 pandemic ( 33 ). Social support from family or friends could also affect University students' mental health problems ( 34 ). Therefore, longitudinal methods should be employed to further address temporal changes in their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, family and friends social support was found to be a protective factor against mental health distress. Recent studies found that a greater degree of family and friends social support was associated with less depressive symptoms; social support from friends alleviated the effect of anxiety, stress, and depression during the COVID-19 pandemic (Woon et al, 2020 ; Woon et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors were investigated in the literature and showed significant association with individuals psychological well-being. A study surveyed 316 participants found that disruption of daily routine was associated with worse depression and anxiety symptoms [21]. Furthermore, social support of peers was associated with milder stress and depression during quarantine, additionally females were more likely to be anxious while less probably to be depressed during this unpleasant experience [22]…”
Section: Discussionmentioning
confidence: 99%